Cities of Refuge in the Middle East : Bringing an Urban Lens to the Forced Displacement Challenge - World Bank (World Bank, Washington, DC, 2017)
This policy note aims to advance our understanding of urban forced displacement, induced by conflict, by looking at the issue from the perspective of receiving towns and cities. It explores why we need a different approach to addressing urban forced displacement; how to “think differently” about urban forced displacement along the humanitarian-development assistance spectrum; what we can learn from existing urbanization and other relevant experiences to inform humanitarian and development responses; and what “thinking differently” means for local, national, and international development actors. The primary audiences of the note are development and humanitarian practitioners as well as policy makers who are increasingly confronted with the urban dimensions of protracted forced displacement.